Epidemiology and Outcomes of Invasive Candidiasis Due to Non-albicans Species of Candida in 2,496 Patients: Data from the Prospective Antifungal Therapy (PATH) Registry 2004–2008 - Pfaller, Michael A.; Andes, David R.; Diekema, Daniel J.; Horn, David L.; Reboli, Annette C.; Rotstein, Coleman; Franks, Billy; Azie, Nkechi E. (PLOS ONE, 2014)
This analysis describes the epidemiology and outcomes of invasive candidiasis caused by non-albicans species of Candida in patients enrolled in the Prospective Antifungal Therapy Alliance (PATH Alliance) registry from 2004 to 2008. A total of 2,496 patients with non-albicans species of Candida isolates were identified. The identified species were C. glabrata (46.4%), C. parapsilosis (24.7%), C. tropicalis (13.9%), C. krusei (5.5%), C. lusitaniae (1.6%), C. dubliniensis (1.5%) and C. guilliermondii (0.4%); 111 infections involved two or more species of Candida (4.4%). Non-albicans species accounted for more than 50% of all cases of invasive candidiasis in 15 of the 24 sites (62.5%) that contributed more than one case to the survey. Among solid organ transplant recipients, patients with non-transplant surgery, and patients with solid tumors, the most prevalent non-albicans species was C. glabrata at 63.7%, 48.0%, and 53.8%, respectively. In 1,883 patients receiving antifungal therapy on day 3, fluconazole (30.5%) and echinocandins (47.5%) were the most frequently administered monotherapies. Among the 15 reported species, 90-day survival was highest for patients infected with either C. parapsilosis (70.7%) or C. lusitaniae (74.5%) and lowest for patients infected with an unknown species (46.7%) or two or more species (53.2%). In conclusion, this study expands the current knowledge of the epidemiology and outcomes of invasive candidiasis caused by non-albicans species of Candida in North America. The variability in species distribution in these centers underscores the importance of local epidemiology in guiding the selection of antifungal therapy.